THE URGENCY OF UNDERSTANDING THE LEGAL SYSTEM IN LEARNING LEGAL SCIENCE - Nopit Ernasari; Zainal Ariffin Hoesein (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
The importance of understanding the basic concepts of the legal system in the context of the study of legal science, the relevance of understanding the legal system as the main foundation for students of legal science in developing knowledge, skills, and in-depth understanding of the legal principles that govern society. The results of the research highlight the critical role of understanding the legal system in forming a holistic perspective on the development of legal science. A deep understanding of the structure, function and dynamics of the legal system provides a solid foundation for students to face the complex challenges of modern legal practice. The implications of this research highlight the need for an emphasis on legal systems understanding as a central element in the design of legal studies curricula to ensure that students not only have a substantial understanding but are also able to integrate and apply legal knowledge in social and practical contexts.